Ethical and Legal Concerns of Artificial Intelligence in the Workplace: Examining Current Legislations in the United States - Rudiyanto, Tri; Kunda, Halley; Dunn, Amy; Shenderovskiy, Sharon; Gibson, Rondarrius (Lex Publica, 2023)
Abstract. The emergence of remote work prompted by the global Covid-19 pandemic has transformed workplace dynamics, highlighting intricate concerns about employee privacy and autonomy. However, the rise of algorithmic management driven by artificial intelligence (AI) challenges the assumed privacy in remote work settings. This paper examines the ethical and legal landscape of AI-powered employee monitoring in the United States. It employs a mixed-methods approach, incorporating literature review, case analysis, legal examination, and ethical analysis. Past cases reveal the complex interaction between personal privacy and employer surveillance, offering insights for current and future legal actions. Current legislation, including the Electronic Communications Privacy Act (ECPA), is explored, along with state-specific laws and their implications. Ethical concerns encompass biometric data tracking, discriminatory biases, and gig economy surveillance. AI’s impact on employee behavior and future implications are discussed, suggesting the need for balanced policies that prioritize transparency, fairness, accountability, and trust. In navigating the challenges of AI-powered monitoring, organizations should consider ethical considerations, existing legislation, and future trends to create a harmonious work environment that respects individual rights. Abstrak. Munculnya kerja jarak jauh yang dipicu oleh pandemi global Covid-19 telah mengubah dinamika tempat kerja, menyoroti keprihatinan rumit tentang privasi dan otonomi karyawan. Namun, munculnya manajemen berbasis algoritma yang digerakkan oleh kecerdasan buatan (AI) menantang privasi yang diasumsikan dalam pengaturan kerja jarak jauh. Makalah ini mengkaji lanskap etika dan hukum dari pemantauan karyawan yang didukung oleh AI di Amerika Serikat. Ini menggunakan pendekatan metode campuran, menggabungkan tinjauan pustaka, analisis kasus, pemeriksaan hukum, dan analisis etika. Kasus-kasus masa lalu mengungkapkan interaksi kompleks antara privasi pribadi dan pengawasan oleh pemberi kerja, memberikan wawasan untuk tindakan hukum saat ini dan masa depan. Undang-undang saat ini, termasuk Undang-Undang Privasi Komunikasi Elektronik (ECPA), dieksplorasi, bersama dengan undang-undang khusus negara dan implikasinya. Keprihatinan etika meliputi pelacakan data biometrik, bias diskriminatif, dan pengawasan ekonomi tumpahan. Dampak AI pada perilaku karyawan dan implikasi masa depan dibahas, menunjukkan perlunya kebijakan yang seimbang yang mengutamakan transparansi, keadilan, akuntabilitas, dan kepercayaan. Saat mengatasi tantangan pemantauan yang didukung oleh AI, organisasi harus mempertimbangkan pertimbangan etika, undang-undang yang ada, dan tren masa depan untuk menciptakan lingkungan kerja yang harmonis yang menghormati hak individu. Kata kunci: Manajemen algoritmik, Pemantauan karyawan yang didukung AI, Privasi, Legalitas, Masalah etika